Local Spatial Development Plans on the Example of Chrzanów (Research Bulletins of the Faculty of Economic Sciences, 2018)
The aim of the article is to analyze selected aspects related to the spatial planning process. This matter will be limited to the lowest level of the yeast what are the municipalities. In the subjective scope, the analysis will be carried out on the example of one of the Małopolska communes, which is Chrzanów. The studies take into account the currently valid spatial development plan in the urban-rural commune of Chrzanów and surveys carried out in 2018. The article uses a dogmatic and legal method and an empirical method - a diagnostic survey; technique: questionnaire, tool: online survey. The article elaborated on the applicable legal acts, the selected literature on the subject and the results of the surveys carried out. The conclusions from the analysis of the above topic will allow to determine the degree of interest of residents in the procedure and assumptions contained in the spatial management plan. An attempt was also made to determine the degree of impact of the plan on the area of ​​the commune.
Keywords: spatial plans; planning; commune; investments; law